Os discursos de Gênero e Sexualidade na Formação de Professoras/es - Souza, Bruno Barbosa de (2018)
Discussions regarding Gender and Sexuality have been receiving more attention in the society, being reflected in a common manner in educational and training environments. With the objective of comprehending how it is being constructed into the teachers‟ initial qualification process, a research was developed in a public university campus, with five licentiate courses: Biological Sciences, Nursing, Languages, Mathematics and Pedagogy. Through a qualitative approach, the objective was to analyze in what manner these courses are developing the Gender and Sexuality issues in the teachers‟ initial qualification process. Pedagogical projects of eighteen licentiate courses, from five university campi, were analyzed. Soon after, we deepened the discussions for a campus of this university and we conducted semi-structured interviews with the students of the last year, of five courses of this campus. Both for research development and for data analysis, the support of the Discourse Analysis was used. The investigation results show that the issue is present in the pedagogical projects of five courses, however, in three of them the issue was inserted only after the law Resolução CNE/CP 02/2015 determined the introduction of the subject into the curriculum of initial qualification courses. Data presented by students indicate that discussions about the issue happen in a specific situation, because of a determined professor or during events. It is also indicated that biology-oriented courses like Biological Sciences and Nursing address the theme with a biological-anatomic view, whereas in Human Science courses like Languages and Pedagogy and Exact Sciences like Mathematics the addressing is wider in their PPs – actions are specific and developed by determined professors.